Penerapan Teknik Token Economy untuk Mengurangi Prokrastinasi Akademik - Nugroho, Aulia Devinn; Haq, Ahmad Arinal; Jamaluddin, Muhammad (Jurnal Konseling dan Psikologi Indonesia, 2025)
This research aims to test the effectiveness of applying the token economy technique in reducing academic procrastination in students. Using an experimental design with a pretest-posttest control group, the research involved 30 students from the class of 2021 from a university in Malang who had a tendency towards high academic procrastination. Subjects were divided into an experimental group that received token economy technique treatment and a control group without treatment. Data was collected using the academic procrastination scale, observation and interviews. The results of analysis using the paired t test showed a significant decrease in the experimental group's academic procrastination score after treatment, while the control group experienced an increase in score. These findings confirm the effectiveness of token economy techniques in reducing academic procrastination, in line with the principle of positive reinforcement in operant conditioning theory. This research makes an important contribution to the development of interventions to address academic procrastination in higher education settings.